The Effect of Jigsaw Method on Reading Comprehension in Non-Major English Basic Science Students - Nurjannah Nurjannah; Mei Hardiah; Muhammad Fadhli (UNIB Press, 2023)
This quasi-experimental research aimed at identifying the effect of Jigsaw Method on students’ reading comprehension in non-major English basic science students at University of Bengkulu. The sample of this research was 78 students from nursing class who took general English courses at Bengkulu University at Academic Year 2022/2023, the students were divided into experimental group (38) from class 2A Nursing and controlled group (40) from class 2B Nursing. The data were collected by using a valid and reliable test which consists of 30 items which represent 5 aspects of reading comprehension that is main idea, detail questions, references, inference, and vocabulary. Furthermore normality and homogeneity data has been checked before the data were analyzed statistically. The paired sample test results indicate that there was a significance improvement (0.000) in students reading comprehension in experimental group, but no significance improvement were found in controlled group (0.735). Furthermore, the result of independent sample test revealed that the reading comprehension achievement of the students in experimental group were significantly (0.000) better than that of those in controlled group. The result showed students who study using expert groups were able to discuss freely with one another. This result suggests that Jigsaw Method was appropriate to be implemented to improve reading comprehension for students in non-major English basic science.